Theory of mind : development in children, brain mechanisms and social implications - Sherwood, Elizabeth, 1972- (Perspectives on cognitive psychology., 2015)
We live at the dawn of a revolution in human interrelatedness. Technological advancements in communication demand interrelatedness not only with family, friends and colleagues but also with Facebook, Twitter and LinkedIn connections. Perhaps this demand has contributed to the resurgence of efforts toward unity across social divisions toward social justice. But even as forces for solidarity are at work in the world, forces against solidarity threaten our existence and some forces work both for and against solidarity. One such force is the very nature of our humanity and in particular the role o.